2021
DOI: 10.3390/w13223251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stepwise Adjustment of C/N during the Start-Up of Submerged Membrane Bioreactors (SMBRs) on the Aerobic Denitrification of Wastewater

Abstract: Based on the improved high-efficiency sewage treatment performance of submerged membrane bioreactors (SMBRs), we focused on how to adjust the C/N ratio of the influent water during reactor start-up to prevent an excessive C/N ratio from causing membrane fouling. In this study, an experimental method of gradually adjusting the influent C/N ratio to quickly start the reactor was proposed, and the results showed that biofilm formation in R1 (SMBR, three influent C/N ratios of 5, 10, and 20) was approximately comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Correlation heat map analysis (Figure 5B) showed that Rhodanobacter was positively correlated with C/N and EC and negatively correlated with the pH. This was consistent with previous studies on Rhodanobacter [40,41]. This result indicated that the growth of Rhodanobacter requires the environment to provide sufficient sources of carbon and a suitable pH.…”
Section: The Correlation Between Microbial Action and Environmental F...supporting
confidence: 90%
“…Correlation heat map analysis (Figure 5B) showed that Rhodanobacter was positively correlated with C/N and EC and negatively correlated with the pH. This was consistent with previous studies on Rhodanobacter [40,41]. This result indicated that the growth of Rhodanobacter requires the environment to provide sufficient sources of carbon and a suitable pH.…”
Section: The Correlation Between Microbial Action and Environmental F...supporting
confidence: 90%
“…Wastewater must contain sufficient organic matter in both quantity and quality for biological nutrient removal processes to occur. Heterotrophic microorganisms responsible for phosphorus removal also require sources of carbon/energy; thus, a higher C/N ratio is needed to achieve the simultaneous removal of nitrogen and phosphorus [37,63,64].…”
Section: Simultaneous Nitrification and Denitrification (Snd)mentioning
confidence: 99%
“…At the same time, the NO 3 − -N concentration in the effluent increased gradually and was maintained at 20.20 ± 1.15 mg/L. It might be that the concentration of organic matter in urban sewage was too low, which led to the inactivation of denitrifying bacteria and the loss of electron donors, resulting in the inhibition of denitrifying bacteria [36]. In the whole process, NH 4 + -N was efficiently and stably removed, indicating that the SMBR was in an efficient denitrification state since its successful start-up.…”
Section: Nitrogen and Tp Monitoringmentioning
confidence: 99%